Optimalisasi Motorik Halus Anak TK melalui Kegiatan Kreatif Membuat Kerajinan Berbasis Daur Ulang - Ni Kadek Rina Pratiwi; Luh Made Dwi Wedayanthi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focused on improving fine motor development in early childhood through creative learning activities that utilize recycled materials, designed and implemented using the ADDIE instructional model. The study involved children from class B2 at TK Prawidya Darma and was conducted systematically through five stages, namely analysis, design, development, implementation, and evaluation. Throughout the learning process, children were engaged in a variety of hands-on craft activities, including cutting, folding, gluing, and assembling recycled objects, which were intentionally structured to train hand–eye coordination, finger flexibility, and concentration. The results demonstrate that learning activities based on recycled materials offer rich and meaningful experiences for young learners. Children showed noticeable improvements in accuracy, independence, and creative expression while completing tasks. In addition, the use of recycled materials helped cultivate environmental awareness from an early age, as children learned the value of reusing everyday objects. The classroom atmosphere became more interactive and enjoyable, with students actively participating and showing enthusiasm during the activities. Overall, the findings indicate that creative recycling-based activities are effective in supporting fine motor skill development through enjoyable, practical, and environmentally friendly learning experiences. This study concludes that integrating recycled materials into creative activities can be an innovative, sustainable, and pedagogically valuable approach for early childhood education programs.